2022
DOI: 10.3389/fpsyg.2021.747168
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept as a Mediator of the Relation Between University Students’ Resilience and Academic Achievement

Abstract: Academic achievement is a factor of interest in both psychology and education. Determining which factors have a negative or positive influence on academic performance has produced different investigations. The present study focuses on analyzing the relationship between resilience, emotional intelligence, self-concept and the academic achievement of university students. For this purpose, different self-report tools were administered to a sample of 1,020 university students from Southern Spain. The Structural Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
3
14
0
2
Order By: Relevance
“…Compared with other dimensions, the results suggested that only the dimension of UOE could play a significant mediating role between BPNS and academic engagement. The finding was in line with a study more recently carried out by Parent-Lamarche (2022). Based on a sample of 254 Canadian employees from 18 small and medium organizations during the COVID-19 pandemic, Parent-Lamarche (2022) found that except for skill utilization and recognition, use of emotion could appear to be key considerations for organizations that wish to increase work engagement and decrease intention to quit.…”
Section: Main Findingssupporting
confidence: 86%
“…Compared with other dimensions, the results suggested that only the dimension of UOE could play a significant mediating role between BPNS and academic engagement. The finding was in line with a study more recently carried out by Parent-Lamarche (2022). Based on a sample of 254 Canadian employees from 18 small and medium organizations during the COVID-19 pandemic, Parent-Lamarche (2022) found that except for skill utilization and recognition, use of emotion could appear to be key considerations for organizations that wish to increase work engagement and decrease intention to quit.…”
Section: Main Findingssupporting
confidence: 86%
“…In line with previous research [ 14 , 56 ], the results obtained have found a positive relationship between EI and coping strategies and a negative relationship between EI and levels of anxiety, depression and stress. In this regard, EI may be associated with adaptive coping strategies in response to the burden of negative emotions that may have been produced by the pandemic and the confinement derived from it.…”
Section: Discussionsupporting
confidence: 92%
“…The concept of EI and its definition have been widely discussed and argued from both the field of education and psychology, with different approaches [ 14 , 15 , 16 ]. In the scientific literature, two opposing models have been identified: the ability model, which considers EI to be a genuine intelligence that allows the person to adapt to the context, and the mixed models, where EI is understood as a set of traits that can vary more or less over time and that determines the person’s behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ante lo declarado, podemos indicar que es necesario fomentar el desarrollo de la resiliencia en los estudiantes para ampliar su habilidad de afrontar de manera exitosa las situaciones complejas y escenarios competitivos al que se enfrentan en la vida universitaria [27], [28], [29]. Se propone a la resiliencia como una habilidad que deben desarrollar lo s estudiantes, fundamentado en que todas las personas tienen fortalezas que se pueden usar para inhibir o moderar los efectos de los factores de riesgo [12], [30].…”
Section: Marco Teóricounclassified